STRATEGI KEPEMIMPINAN KEPALA SEKOLAH DI ERA DIGITAL DALAM MENUMBUHKAN IKLIM INOVASI DAN LOYALITAS GURU DI UPTD SDN 399 SIWA - Besse Herlina; Eka Mayasari; Haliati; Hasnidar; Nursanti; Ridhah Rachman; Syamsuriadi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The purpose of this study is to evaluate the leadership strategies of the school principal in the digital age to enhance innovation and teacher commitment at UPTD SDN 399 Siwa. The development of digital technology requires school principals to act not only as administrators but also as astute leaders capable of adapting to technology, fostering innovation in learning, and strengthening teachers’ commitment to the school. A qualitative descriptive method was used in this study, which collected data through observation, interviews, and documentation. The research sample consisted of the school principal and teachers from grades one through six. Triangulation techniques were used to test data validity. The results indicate that school principals who demonstrate the use of technology, provide opportunities for participation, and support teachers’ professional development can enhance teachers’ sense of ownership, commitment, and performance. Humanistic, participatory, and digital technology-based leadership are key factors in creating an innovative school environment and enhancing teacher loyalty. Mentoring strategies and a phased approach have proven effective in overcoming barriers such as disparities in digital literacy and resource limitations.